MEDIA PEMBELAJARAN CD INTERAKTIF UNTUK SISWA SEKOLAH DASAR - Susi Susanti (LPPM STAI Muhammadiyah Probolinggo, 2023)
Learning media can make it easier for students to understand the material presented. With the development of the media era, it is possible to take advantage of increasingly modern technology, but schools still rarely use learning media in their learning. This research and development aims to produce a product in the form of an CD interactive media and to test the feasibility of an interactive CD media product on the sub-themes I and my dreams with the Microsoft PowerPoint for the fourth grade elementary school students. This research was conducted at SDN Kacangan I Lamongan with a class IV research sample. This research is a development research that uses the modified Borg and Gall development research model. The results of this study are learning media in the form of Interactive CDs and based on the results of product trials by material experts and media experts, the product has a decent criteria with a percentage of 90%. Based on the product trial on a limited scale, the product received the eligible criteria with a percentage of 79,4%. Based on these results, the Interactive CD learning media on the sub-themes I and my ideals is suitable for use in learning. Keyword: Learning media, CD interactive, sub-themes I and my ideals